Longitudinal Associations between Different Types of Sexting, Adolescent Mental Health, and Sexual Risk Behaviors: Moderating Effects of Gender, Ethnicity, Disability Status, and Sexual Minority Status. - Wright, Michelle F.; Wachs, Sebastian (Archives of Sexual Behavior, 2024)
The present study investigated the moderating effect of adolescent demographic variables in the longitudinal associations among different types of sexting, mental health (i.e., depression, self-harm, subjective health complaints), and sexual risk behaviors. There were 1113 adolescents (ages 14–17 years; Mage = 16.36; SD =.81; 50% female) from six high schools located in the United States included in this study. Adolescents completed questionnaires on their sexting behaviors, mental health, and sexual risk behaviors during the ninth grade; in tenth grade, they completed questionnaires on mental health and sexual risk behaviors. Non-consensual sexting and pressured sexting were both related positively to each of the mental health variables and sexual risk behaviors. The relationship between non-consensual sexting and depressive symptoms was stronger for girls, ethnic minorities, those adolescents with disabilities, and sexual minorities. Similar patterns were found for pressured sexting, non-suicidal self-harm, and subjective health complaints. The relationships between pressured sexting and sexual risk behaviors were stronger for girls, ethnic minorities, those adolescents with disabilities, and those who identified as sexual minorities. Research focused on the relationships among different types of sexting, mental health, and sexual risk behaviors is important as such research facilitates the development of evidence-based recommendations for sexting harm prevention and sexual education programs.